Politics and Policy of Islamic Education during the Old Order Era: A Study of the Role of the Ministry of Religion, Islamic Religious Colleges (PTKI), and the Implementation of the National Education System Law - Hukma Fikria Adira; Ahmad Ahmad Arifi; Sabarudin Sabarudin (Institut Agama Islam An-Nawawi Purworejo, 2026)
Islamic education during the Old Order era is a crucial issue in the history of Indonesian education because it developed amidst the country's unstable political dynamics, the ideological struggles of nationalism, Islam, and communism, and the initial efforts to establish a national education system after independence. This topic is relevant to study because Islamic education policies during the 1945–1966 period not only determined the position of madrasahs, religious studies, and Islamic Religious Colleges (PTKI) within the national system, but also laid the foundations that have been influential to this day. This study aims to analyze the politics and policies of Islamic education during the Old Order era by highlighting the influence of national political dynamics, the strategic role of the Ministry of Religious Affairs, the process of establishing and developing PTKIs, the regulation of religious studies in the National Education System Law, and the challenges and opportunities faced by Islamic education during that period. This study uses a qualitative, field-study design combined with historical studies. Data were collected through in-depth interviews, observations, documentation studies, and literature reviews of archives, regulations, and institutional records. Then, they were analyzed interactively and thematically through the stages of data reduction, data presentation, and drawing conclusions using source and method triangulation. The results of this study indicate that Islamic education policy during the Old Order era was heavily influenced by the country's political configuration and tended to be compromising. The Ministry of Religious Affairs proved to be a key actor in maintaining the existence of madrasahs, expanding religious instruction in public schools, and building the foundation of Islamic higher education through PTKI (Islamic Higher Education Institutions). This study also found that the regulation of religious instruction in Law No. 4 of 1950 in conjunction with Law No. 12 of 1954 reflected a form of state accommodation to Islamic aspirations, but did not fully guarantee substantive equality in its implementation. This finding contributes to the study of the politics of Islamic education by demonstrating that the development of Islamic education was the result of negotiations between the state, religion, and society, not merely a pedagogical process. Thus, this study concludes that the Old Order era was a crucial phase that shaped the institutional and political foundations of Islamic education in Indonesia.